MUSIC THERAPY IN PHYSICAL TREATMENT - Wellington Ferreira Fontes, Gilton (Revista Gênero e Interdisciplinaridade, 2023)
This article will present music therapy as a therapeutic method of intervention for people undergoing treatment and recovery from physical illnesses, during hospitalization or after, where, through scientific research based on comprehensive literature, it will seek to highlight the importance of the theme. . The biopsychosocial benefits will be investigated, discussing this method of intervention with a view to the development of better mental, cognitive and motor health conditions, scientifically explaining that at the same time they will be reflected in physical health. The research will point out that music exerts influences regarding the expression of the human being and its biological interaction with the environment, that the sounds are present for the individual since his intrauterine life, and, propitiates the reflection and exteriorization of the feelings, promoting well-being mental and physical. The search in the various bibliographic data will qualitatively bring the importance of the research carried out, where the benefits of applying music therapy in the hospital or post-hospital environment for physical treatments will be pointed out. It will be scientifically understood that music therapy is an effective technique to enable biopsychosocial growth and development, achieving the objectives of alleviating symptoms in various illnesses.